2011
DOI: 10.1016/j.technovation.2011.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Differences in technology transfer between science-based and development-based industries: Transfer mechanisms and barriers

Abstract: Although several studies in the wide body of literature on technology transfer have hinted at differences across industries, this still remains an understudied issue. Our study addresses this topic and considers to what degree technology transfer processes differ across different industrial sectors. To that end, we study to what extent technology transfer processes differ along both types of transfer mechanisms and key barriers inhibiting the transfer process. Based on a survey of Dutch practitioners on both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(74 citation statements)
references
References 47 publications
1
61
0
8
Order By: Relevance
“…Specifically, the interaction process and knowledge transfer perspective explores different types of U-I interaction channels and their effectiveness in terms of achieving short-term or long-term goals (De Fuentes and Dutrenit 2012). Correspondingly, organisational and cultural barriers that may impede the interaction process are presented in different configurations (Gilsing et al 2011;Kyoung-Joo 2011). The U-I interactions and associated outcomes in the form of knowledge transfer are explored from a dynamic viewpoint, resulting in options to manage and mechanisms to adjust the interactions, ranging from the early cut-off interactions to sustained interactions (Treibich et al 2013).…”
Section: Cluster 5: Interaction Process and Knowledge Transfer Perspementioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the interaction process and knowledge transfer perspective explores different types of U-I interaction channels and their effectiveness in terms of achieving short-term or long-term goals (De Fuentes and Dutrenit 2012). Correspondingly, organisational and cultural barriers that may impede the interaction process are presented in different configurations (Gilsing et al 2011;Kyoung-Joo 2011). The U-I interactions and associated outcomes in the form of knowledge transfer are explored from a dynamic viewpoint, resulting in options to manage and mechanisms to adjust the interactions, ranging from the early cut-off interactions to sustained interactions (Treibich et al 2013).…”
Section: Cluster 5: Interaction Process and Knowledge Transfer Perspementioning
confidence: 99%
“…The process perspective (interaction process and knowledge transfer cluster) of U-I collaborations is not a core research stream; however, there is a strong need for future examinations, especially if we want to understand the complex processes of interaction between academia and industry, resulting in a long-term exchange of knowledge and technological resources at all levels of U-I collaboration (Gilsing et al 2011). In line with McMullen and Dimov (2013), there are a number of conceptual questions that require answers if a process perspective to U-I collaborations shall gain momentum: What is the U-I collaboration journey, when has this journey started, when has this journey concluded, does it require particular interactions to progress; and what remains constant and what changes throughout the process of interaction between U-I partners?…”
Section: The Institutions In University-industry Collaborationsmentioning
confidence: 99%
“…According to Gilsing et al (2011), it has been demonstrated how a wide range of factors affects the transfer of technological knowledge from universities to industry. on knowledge and skills these organizations have (Ranga & Etzkowitz (2013) to become, consequently, the main innovation suppliers Borrell-Damian, 2010).…”
Section: Technology Transfermentioning
confidence: 99%
“…But, even though technology were a commodity, transference is not a gentle process [16,17]. First, recipients must choose where to take technology from or where to get ideas to improve their processes.…”
Section: Economic Development: From Technology Transfer To Knowlementioning
confidence: 99%